SUBTITLING STRATEGIES OF THE SONGS TRANSLATION IN THEMOVIE ENTITLED “PITCH PERFECT” - Kholiq, Muh; Soraya, Grace (UG Journal, 2022)
Subtitling is the process of translating the source language into the target language in audio-visual. This research aimed to find out the subtitling strategies found in songs played in a movie entitled Pitch Perfect. This research used a qualitative descriptive method with a literature study approach. The result of the research showed that there are 6 strategies found in the subtitling strategies used in the songs of the movie namely transfer, paraphrase, dislocation, condensation, decimation, and resignat ion. The most used strategy in this research is transfer strategy with 55.84% of the total data collected, followed by dislocation strategy with 14.28% of the total data collected, followed by paraphrase with 10.5% of the total data collected, followed by condensation with 6.5% of the total data collected, followed by decimation with 2.6% of the total data collected, and finally, last but not least, resignation with 1.3% of the total data collected.